Towards two-dimensional color tunability of all-solid-state electrochromic devices using carbon dots - Li, Chen; Zhen, Mingshuo; Sun, Boshan; Hong, Yingping; Xiong, Jijun; Xue, Wenzhi; Li, Xiaohua; Guo, Zhongkun; Liu, Lei (Frontiers in Chemistry, 2022)
Electrochromic devices (ECDs) that display multicolor patterns have gradually attracted widespread attention. Considering the complexity in the integration of various electrochromic materials and multi-electrode configurations, the design of multicolor patterned ECDs based on simple approaches is still a big challenge. Herein, it is demonstrated vivid ECDs with broadened color hues via introducing carbon dots (CDs) into the ion electrolyte layer. Benefiting from the synergistic effect of electrodes and electrolytes, the resultant ECDs presented a rich color change. Significantly, the fabricated ECDs can still maintain a stable and reversible color change even in high temperature environments where operating temperatures are constantly changing from RT to 70 ℃. These findings represent a novel strategy for fabricating multicolor electrochromic displays and are expected to advance the development of intelligent and portable electronics.